SARS-CoV-2: a preliminary comparative epidemiological analysis between Brazil and the World - Sibajev, Alexander; Bassoli , Bruna Kempfer; Benedetti , Maria Soledade Garcia; Camargo , Mariana Cristina Rodrigues; Camargo , Rodrigues; Ferreira , Barbara Gomes; Santana, Camila Sampaio Florença; Vaz , Edla Mayara Fernandes; Segheto, Raphael Silva; Caetano, Silvio José Portinho; Camargo, Calvino (Revista Saúde & Diversidade, 2020)
Introduction: The world is facing a public health emergency due to the pandemic of the new coronavirus (SARS-CoV-2) and on March 20th, 2020, COVID-19, the disease caused by this virus, was considered to be community transmission throughout Brazil. As the incidence, mortality and lethality of COVID-19 are not homogeneous for all countries or regions within the same country, it is essential to monitor the profile of epidemiological indicators in Brazil in relation to the world. Objective: This research aims to know the epidemiological characteristics of the COVID-19 pandemic, comparing data from Brazil with the total world data from countries with registered cases. Methods: The data used to calculate the incidence, mortality, lethality, percentage of recovered and active cases were obtained from Johns Hopkins University & Medicine Coronavirus Resource Center, between March 23rd and April 21st of 2020, totaling 30 days. Statistical tests of correlation and comparison of means were used to evaluate the relationship between incidence and mortality rates, the evolution of the epidemiological indicators over time and to make a comparison between Brazil and the world. Results: The curves of incidence, mortality, lethality and percentage of cases recovered in Brazil and in the world were relatively parallel at first, with lower values for Brazil compared to the world (p < 0.05). Unlike the other indicators, the percentage of the active cases was higher in Brazil than in the world (p < 0.05). There was also a trend of approximation of the curves throughout the evaluated period and a directly proportional positive correlation between incidence and mortality rates in the world and in Brazil (p < 0.05). Conclusion: The data analysis showed an expansion of the COVID-19 epidemic in Brazil, revealing the importance of establishing preventive measures aiming to control the infection rate by flattening the epidemiological curves and, finally, avoiding the collapse of local and regional health services.